FLIPPED CLASSROOM: INNOVATIVE LEARNING TO INCREASE THE LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS IN THE DIGITAL AGE - Jamilah Jamilah; Tri Sukitman; Mulyadi Mulyadi; Jamilah (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2021)
Today's digital age has an important impact on education. One of the learning models to increase the motivation of learners in learning in the digital era is flipped learning with reverse learning models. This research is a type of literature research. This research data source uses a variety of literature from various journals. Data analysis in this study uses content analysis. The results of this study show that the application of flipped classroom in the digital era has been able to increase students' learning motivation both at school and at home. Because students have studied the learning material before entering the class which means that the teacher is no longer dominant in controlling the class so that the interaction between the teacher and students becomes better and is very enjoyable in learning. Therefore when designed effectively, the flipped classroom method can increase the students' motivation towards the course. Also, suggestions for practitioners were discussed in this study